The Legislative Competence of the Head of State in a Paliamentary System- Comparative Analytical Study Between the Constitution of the Republic of Iraq of 2005 and the Draft Constitution of the Kurdistan Region of Iraq - Weisy, Osman Ali Hassan (Journal of Legal and Political Studies, 2021)
The parliamentary system is a structure of cooperation between various authorities, and the political system in the Iraqi constitution and the draft constitution of the Kurdistan Region - Iraq are representative mechanisms within the parliamentary system, as the head of state can exercise his power according to the requirements of the parliamentary system. The executive authority, including the head of state, can participate in the law-making process, which includes different stages: it begins with pre-legislative scrutiny and consultation process and then a bill may be introduced formally before it becomes law. The Constitution of the Republic Iraq of 2005 does not include the balance between the legislative and executive powers. It does not grant the executive authority the power to dissolve the House of Representatives, and despite the president's power to submit draft laws to the House of Representatives, the President of the Republic does not have the authority to exercise his right to submit legal decisions or request an adjournment or reject a law issued by the House of Representatives, and this to maintain the required balance between the two powers. In addition, recent amendments to articles of the Iraqi constitution regarding the ratification and issuance of laws – decide by the Federal Supreme Court in Iraq - rendered these arrangements ineffective. As for the draft constitution of the Kurdistan Region - Iraq of 2009, and despite the absence of equilibrium between the legislative and executive powers, and the fact that the executive authority does not have the power to dissolve the parliament, it empowered the president of the Kurdistan Region to engage in the legislative process in both normal and extraordinary circumstances.
Keywords: parliamentary system; political system; executive authority; lawmaking process; prelegislative scrutiny